Assessment of the Earliness of Detection and Notification of Major Infectious Threats to Global Health Security in Benin - SODJINOU, Vincent Dossou; AYELO, Paul Ahoumènou; SALAMI, Lamidhi; KPOZEHOUEN, Alphonse; OUENDO, Dona Edgard-Marius (Archives of Clinical and Biomedical Research, 2022)
Introduction Early detection and notification can reduce morbidity and mortality from an event. Objective The study assessed the earliness of the detection and the notification of major global health security threats in Benin. Methods The study was a cross-sectional, descriptive, and analytical. Non-probability sampling and purposive selection of five prone epidemic diseases were used. The earliness of the detection was considered good if at least 80% of cases were detected within 48 hours. This was considered acceptable if at least 80% of cases were detected after 48 hours and before one incubation period of the disease. If none of the two conditions was met, the detection earliness was rated insufficient. The earliness of the notification was judged good if at least 80% of cases were notified within 48 hours. Otherwise, it was deemed insufficient. Results The early detection of major infectious threats to global health security in Benin was insufficient. No disease threats were detected within 48 hours from 2016 to 2020. Only 72.21% of cases were detected before one incubation period of the selected diseases. Early detection was acceptable for Lassa virus fever and measles. Also, early notification was insufficient. Only 66.22% of cases were notified within 48 hours. The early notification was good for cholera (81.73%), yellow fever (82.13%) and measles (84.14%). Conclusion Improving rapid access to health services, scaling up electronic reporting and building the capacities of stakeholders on global health security issues are potential means of improvement of detection and notification.